2022
DOI: 10.3390/insects13010083
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Very Long-Chain Hydrocarbons and the Incorporation of Body Surface Area Metrics Reveal Novel Perspectives for Cuticular Profile Analysis in Insects

Abstract: Most of our knowledge on insect cuticular hydrocarbons (CHCs) stems from analytical techniques based on gas-chromatography coupled with mass spectrometry (GC-MS). However, this method has its limits under standard conditions, particularly in detecting compounds beyond a chain length of around C40. Here, we compare the CHC chain length range detectable by GC-MS with the range assessed by silver-assisted laser desorption/ionization mass spectrometry (Ag-LDI-MS), a novel and rarely applied technique on insect CHC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In a previous study, chemical profiles analyzed among the same taxa were found to be solely discriminable on the species level, rather than on the colony (termites) or population (cockroaches) level (Golian et al., 2022 ). Therefore, we restricted ourselves to two respective laboratory colonies per termite species and two respective laboratory populations per cockroach species.…”
Section: Methodsmentioning
confidence: 98%
“…In a previous study, chemical profiles analyzed among the same taxa were found to be solely discriminable on the species level, rather than on the colony (termites) or population (cockroaches) level (Golian et al., 2022 ). Therefore, we restricted ourselves to two respective laboratory colonies per termite species and two respective laboratory populations per cockroach species.…”
Section: Methodsmentioning
confidence: 98%
“…Future studies should also consider the occurrence of very-long chained CHC compounds of up to C58 in Blattodea surface profiles as recently demonstrated with non-standard analytical methods (Golian et al 2022). However, neither exact compound quantifications nor identifications (e.g., discrimination between n -alkanes and methyl-branch alkanes) are so far possible in this higher chain length range extending beyond the CHC compounds traditionally accessed and identified through gas-chromatographic separation (Schnapp et al 2016;Bien et al 2019).…”
Section: Chc-based Communication Mechanisms and Outlook For Future St...mentioning
confidence: 95%
“…In a previous study, chemical profiles analyzed among the same taxa where found to be solely discriminable on the species level, rather than on the colony (termites) or population (cockroaches) level (Golian et al 2022). Therefore, we restricted ourselves to two respective laboratory colonies per termite species and two respective laboratory populations per cockroach species.…”
Section: Tested Termite and Cockroach Speciesmentioning
confidence: 99%
“…Depending on the insect species, the cuticle is considered to contain an outermost “waxy layer” with various long-to-mid-chain hydrocarbons, including alkanes, alkenes, and their methyl-branched derivatives, fatty acids and esters, alcohols, ketones, and aldehydes, as well as minor components, including triacylglycerols, epoxides, and ethers (Chung and Carroll 2015 , Golian et al 2022 ) (Fig. 2 ).…”
Section: Cross-talk: During Fungal Cuticle Contact and Penetrationmentioning
confidence: 99%